The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0102-261x2005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Teores de potássio, urânio, tório e taxa de produção de calor radiogênico no embasamento adjacente às bacias sedimentares de Camamu e Almada, Bahia, Brasil

Abstract: ABSTRACT.The bedrock adjacent to Camamu and Almada sedimentary basins is characterized mainly by rocks of granulite and amphibolite facies, with archean and paleoproterozoic ages, which belong to orogen Itabuna-Salvador-Curaçá. The units in major proportion in this context are the metatonalites associated with basic and metamonzonites belonging to Itabuna belt. In smaller area occur the Teolândia granite and the Moenda granodiorite associated with the Ipiaú band amphibolites, the charnockites and charnoenderbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
1
2
0
4
Order By: Relevance
“…The relatively large values of standard deviations of the mean values are considered as indicative of the compound effects of variations related to soil types and lithologic units. These values are in reasonable agreement with results of laboratory measurements on borehole samples of Proterozoic sedimentary sequences reported by Roque and Ribeiro (1997), lead isotope studies in some localities of the São Francisco structural province reported by Iyer et al (1984) and gamma spectrometric measurements of basement rock samples of the Atlantic coastal basins by Sapucaia et al (2005).…”
Section: Airborne Gamma Surveysupporting
confidence: 91%
See 1 more Smart Citation
“…The relatively large values of standard deviations of the mean values are considered as indicative of the compound effects of variations related to soil types and lithologic units. These values are in reasonable agreement with results of laboratory measurements on borehole samples of Proterozoic sedimentary sequences reported by Roque and Ribeiro (1997), lead isotope studies in some localities of the São Francisco structural province reported by Iyer et al (1984) and gamma spectrometric measurements of basement rock samples of the Atlantic coastal basins by Sapucaia et al (2005).…”
Section: Airborne Gamma Surveysupporting
confidence: 91%
“…It has also been used for mapping area extent of geologic rock formations associated with such radioactive elements. Examples of such studies carried out in Brazil include the works of Blum et al (2003) and Sapucaia et al (2005). Measurements of gamma radiation at ground level provide information on the abundances of radioactive elements in the top soil layers.…”
Section: Introductionmentioning
confidence: 99%
“…Rochas de composição mineralógica caracterizada essencialmente por quartzo e plagioclásio apresentam baixas concentrações de K, U e Th, enquanto que as rochas compostas por micas, feldspatos e minerais acessórios como o zircão, a apatita e a monazita, contêm teores maiores desses elementos (SAPUCAIA et al, 2005). Alguns minerais acessórios portadores de Th e U podem ser citados, como zircão, titanita, epidoto primário, monazita, apatita, xenotima e allanita (ULBRICH, 2009).…”
Section: Resultsunclassified
“…Sighinolfi and Sakai 1977;Ferreira et al 1979Ferreira et al , 1992Hamza 1980;Iyer et al 1984;Vitorello et al 1980;Roque and Ribeiro 1997;Sapucaia et al 2005). The experimental techniques employed include both gamma ray spectrometry as well as isotope mass spectrometry.…”
Section: Radiogenic Heat Productionmentioning
confidence: 99%